KEANEKARAGAMAN JENIS JAMUR MAKROSKOPIS DI ARBORETUM SYLVA UNIVERSITAS TANJUNGPURA - Annisa, Iin; Ekamawanti, Hanna Artuti; Wahdina, . (JURNAL HUTAN LESTARI, 2017)
Macroscopic fungi have an important role for human life, economic aspect, food requirement, medicine, educational and science aspect. The study aims to record the species diversity of macroscopic fungi at arboretum Sylva Universitas Tanjungpura. The researcher time was conducted for two weeks in May 2017 using Purposive Sampling method. Result of research from all 0,0625 ha found 30 species of macroscopic fungi from with the total of 1.652 individuals from 21 genus and 12 families. The 12 families found included: Polyporeacea, Ganodermaceae, Rigidoporaceae, Cortinariaceae, Auriculariaceae, Coprinaceae, Sclerodermataceae, Agaricaeae, Schizophyllaceae, Phallaceae, dan Geastraceae. The fungi from the most Polyporaceae family are found at arboretum Sylva Universitas Tanjungpura. The 30 species found, fungi were used as food ingredients of 10%, medicines (13,33%), souvenirs (3,33%), not edible (50%), toxic (10%), and unknow fungi (13,33%). Keyword : Ecological Function, Ectomikoriza, Hexagonia tenuis, Utilization